Antiparasitic and Cytotoxic Activity of Bokkosin, A Novel Diterpene-Substituted Chromanyl Benzoquinone From Calliandra portoricensis - Nvau, John B.; Alenezi, Samya; Ungogo, Marzuq A.; Alfayez, Ibrahim A. M.; Natto, Manal J.; Gray, Alexander I.; Ferro, Valerie A.; Watson, Dave G.; de Koning, Harry P.; Igoli, John O. (Frontiers in Chemistry, 2020)
Calliandra portoricensis is a medicinal plant growing freely in Nigeria. It is used traditionally to treat tuberculosis, as an anthelmintic and an abortifacient. Phytochemical fractionation and screening of its root extracts has yielded a novel (5-hydroxy-7-methoxy-4-oxo-1-chromanyl)-4-methoxy-p-benzoquinone (breverin)-substituted cassane diterpene, which was designated bokkosin. It was obtained from column chromatography of the ethyl acetate extract of the roots. The compound was characterized using IR, NMR (1D and 2D) and mass spectral data. Promising antiparasitic activity was observed against the kinetoplastid parasite Trypanosoma brucei brucei, as well as moderate activity against Trypanosoma congolense and Leishmania mexicana and low toxicity in mammalian cells, with the best in vitro EC50 values against T. b. brucei (0.69 μg/mL against a standard laboratory strain, and its multi-drug resistant clone (0.33 μg/mL). The effect on T. b. brucei in culture was rapid and dose-dependent, leading to apparently irreversible growth arrest and cell death after an exposure of just 2 h at 2 × or 4 × EC50. The identification of bokkosin constitutes the first isolation of this class of compound from any natural source and establishes the compound as a potential trypanocide that, considering its novelty, should now be tested for activity against other microorganisms as well.